The cultural cognition of taste term conflation - Yoshimi Osawa (2018)
Languages vary in the number of descriptive terms for the four basic taste stimuli -sweet, sour, salty, and bitter, and for the glutamate stimulus. Some languages regularly present terms that link sour/bitter, salt/ sweet, and glutamate/salty. However, in other languages where these tastes are lexically encoded speakers vary between each other, and in their ability to use terms consistently. What may seem like confusion we suggest might better be described as conflation resulting from changes in the ecology and culture of food. Moreover, these patterns highlight the underlying dynamic of taste cognition, and how variation associated with taste cognition arises. Using comparative data from secondary sources, free listing tests, and experimental data from a recent study of Japanese and British English speakers, this article seeks to shed light on these issues. © BLOOMSBURY.